Modulações do tempo no audiovisual: dos espaços densos aos tempos espessos - Franco, Carlos Fernando Martins (Universidade do Vale do Rio dos Sinos, 2010)
This research tried to understand framed temporality phenomena inside audiovisual expression. This has begun from Bergson and Deleuze, with these theories that studies time and space, as well as motion pictured expressions authors as Eisenstein, Martin and Aumont. The unconstructing the three classical time dimensions (story time, opera time and perceptual time) has happened simultaneously with the non-cut scene analyses of several expressive materials. This has used the intuitive method by Bergson, which permitted speculate the existence of the forth time dimension beyond the three classical, the object time on a frame, composed by its spiritual time and dynamic time. This has defined, as alternative from rithm concept, the time modulation as an articulation between perceptual and object time, that contains the dynamic interval and spiritual time (durée).
Keywords: Modulação do tempo; Intuição; Percepção; Ritmo; Audiovisual; Motion pictured expressions; Time modulation; Intuition; Perception; Rithm; ACCNPQ::Ciências Sociais Aplicadas::Comunicação